2005
DOI: 10.1016/j.otohns.2004.09.026
|View full text |Cite
|
Sign up to set email alerts
|

Trends in otolaryngology research during the period 1995‐2000: A bibliometric approach

Abstract: OBJECTIVES: To evaluate the distribution and scope of papers published in the world in otolaryngology (ORL) journals and to compare the impact of this research among different countries. METHODS: Papers published in the 29 ORL journals screened by the Institute for Scientific Information (ISI, Philadelphia, PA, USA) in the 6-year period 1995–2000 were considered. The journal impact factor (IF), the source country population, and gross domestic product (GDP) were recorded. All key words, both those assigned by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 12 publications
2
53
0
4
Order By: Relevance
“…Taking into consideration of their GDP, we found that the better the economic ranking of a country the higher the quantity of its biomedical publications. The correlation between research productivity and GDP has received some attention in the past [2,33,[35][36][37][38][39][40]. We recognise that other factors such number of journals, high number of research institutions or universities, and research specialization may also have contributed to the observed high performance of the top 3 countries (South Africa, Egypt, and Nigeria).…”
Section: Main Findingsmentioning
confidence: 99%
“…Taking into consideration of their GDP, we found that the better the economic ranking of a country the higher the quantity of its biomedical publications. The correlation between research productivity and GDP has received some attention in the past [2,33,[35][36][37][38][39][40]. We recognise that other factors such number of journals, high number of research institutions or universities, and research specialization may also have contributed to the observed high performance of the top 3 countries (South Africa, Egypt, and Nigeria).…”
Section: Main Findingsmentioning
confidence: 99%
“…Bunun yanında bilimsel yayınların yer aldığı dergilerin de kalite açısından değerlendirilmelerinde ya da dönemle-re göre öne çıkan araştırma alanlarının saptanmasında bu çalışmalardan yararlanılabilir. [2][3][4][5]7,14,15] Rinoloji, otoloji ya da baş boyun cerrahisi gibi KBB'nin diğer alt dallarıyla karşılaştırıldığında pediatrik KBB ülkemizde oldukça yeni olan bir KBB alt dalıdır. Bu çalışmada Türkiye ve diğer Avrupa ülkelerinin etki faktörü en yüksek olan KBB dergilerinde yer alan yayın sayıları dönemsel olarak araştırılmış, sonrasında da pediatrik KBB alanında ülkemizden yapılan yayınların sayısı diğer Avrupa ülkelerinden yapılanlar ile karşılaş-tırıldı.…”
Section: Discussionunclassified
“…[2,5,10,16] Çalışmamızda bu parametreler göz önüne alınmadı. Ancak araştırmanın bitiş tarihi olan 2012 yılı itibariyle Türkiye nüfus olarak, Rusya ve Almanya'dan sonra Avrupa ülke-leri içinde üçüncü sırada yer alırken, tıp fakültesi sayısı açısından ilk sırada yer almaktadır.…”
Section: Discussionunclassified
See 2 more Smart Citations